Male Osteoporosis - Hanusch, B. C.; Tuck, S. P.; Francis, R. M. (Osteologie, 2013)
Male osteoporosis is common and results in considerable morbidity and mortality. There are distinct differences in the normal aging of bone between the genders, which result in a lower fracture rate in men. Men who suffer from osteoporosis are much more likely than women to have secondary causes. The identification and treatment of these secondary causes, wherever possible, will result in substantial improvements in BMD. There is now evidence for use of many of the existing agents to treat osteoporosis in men. In younger hypogonadal men testosterone replacement is worth considering, but in older men especially the over sixties this is less effective and there is an increased risk of adverse cardiovascular and prostatic outcomes. Prostate cancer is an increasingly common cause, which is partially the result of the success of ADT. There is now good evidence for the use of bisphosphonates and denosumab in this group of patients. HIV, whilst not being specific to men, is an increasingly recognised cause of male osteoporosis. The reasons for this are multifactorial and some may well be attributable to the anti-retroviral therapy itself. There is emerging evidence of an increased fracture risk in HIV infected individuals. The bone loss can be prevented by the use of bisphosphonates.
Keywords: Male osteoporosis; secondary osteoporosis; bone loss; testosterone